Relationship between Fluid Intelligence and Executive Function among University Students in Indonesia - Suryono, Alfina Zalfa; Rohmatullayaly, Eneng Nunuz; Widayati, Kanthi Arum (HAYATI Journal of Biosciences, 2025)
Fluid intelligence is the ability to think logically and abstractly. Executive function is the behavioural ability to coordinate, control and adapt to new situations. Fluid intelligence and executive function play an important role in the ability to solve problems, adapt, and carry out daily behaviour. Previous research states that high fluid intelligence is followed by high executive function. Currently, there are no data regarding the relationship between fluid intelligence and executive function and the socio-demographic factors associated with both variables. Therefore, this study to examine the relationship and socio-demographic factors between fluid intelligence and executive function among university students in Indonesia. This study was conducted using a questionnaire and the zoom platform with a total of 306 university student in Indonesia. First, responders will complete a questionnaire containing demographic information. Second, respondents will be contacted again to assess fluid intelligence using the Baddeley Reasoning Test and executive function measurement using Tower of Hanoi. This study found that fluid intelligence was not substantially linked with planning time. However, high fluid intelligence was strongly related with less mobility and overall time. The socio-demographic component related with fluid intelligence is age. Sociodemographic factors related with executive function include sex, education level, and study discipline, as well as overall time.